2021
DOI: 10.3390/ma14237411
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Optical Properties of the Sunspace Casing as Factors Influencing Temperature Rise in Greenhouse Systems

Abstract: In sunspaces, there is an observable temperature rise above the external air temperature, caused by solar gains and the buffering effect of their enclosure. In addition, their external partitions form a barrier preventing the direct influence of the external environment and delaying the natural deterioration of elevation surface. In the paper, the temperature rise in a glazed balcony attached to a typical flat in a multifamily building, together with the energy demand in the living zone, were assessed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The program was also validated in two ways by one of the authors: according to EN 15265 standard [43], and based on the measurements carried out in the climatic chambers of the Rzeszów University of Technology. The validation procedures were described in detail in [44][45][46].…”
Section: Simulationsmentioning
confidence: 99%
“…The program was also validated in two ways by one of the authors: according to EN 15265 standard [43], and based on the measurements carried out in the climatic chambers of the Rzeszów University of Technology. The validation procedures were described in detail in [44][45][46].…”
Section: Simulationsmentioning
confidence: 99%
“…Installing a solar greenhouse provides additional benefits beyond energy savings, such as enhancing the building's external appearance and offering renovation protection (Grudzinska, 2021). In cold climates, the use of double-glazed glass is recommended for solar greenhouse design, whereas locations with milder winters may suffice with singleglazed glass (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The attached solar greenhouses, which are an open thermodynamic system with energy and mass exchange, receive heat from the sun's rays passing through the glass envelope [10]. The installation of a solar greenhouse also provides additional benefits, not related to energy savings, such as the renovation and weather protection of the building's exterior façade [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ulpiani et al [8] found that in Italy, a greenhouse with convective heat exchange with double glazing and reduced depth reduced daily consumption more than 27%, highlighting how the use of a greenhouse with reduced depth leads to greater savings. Grudzinska [11] achieved energy demand savings of 33% by using a double-glazed envelope with selective coating in Poland. These articles do not investigate the performance using low-e double glazing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation